Caring in the wake of the rising tide: Moral distress in residential nursing care of people living with dementia. (April 2018) - Pijl-Zieber, Em M; Awosoga, Olu; Spenceley, Shannon; Hagen, Brad; Hall, Barry; Lapins, Janet
Objective: Moral distress is increasingly being recognized as a concern for health care professionals. The purpose of this study was to explore the nature and prevalence of moral distress among nursing staff who care for people living with dementia. Methods: This study was focused on nursing staff caring for people with dementia in long-term care and assisted living sites. The Moral Distress in Dementia Care Survey instrument was distributed to 23 sites and nursing staff rated the frequency and severity of situations that were identified as potentially causing moral distress. Results: Moral distress is prevalent in the nursing staff who provide dementia care. Nursing staff reported experiencing moral distress at least daily or weekly. Both frequency and severity of moral distress increased with proximity to (amount of time spent at) the bedside. Moral distress had negative psychological and physiological effects on nursing staff, and affected intention to quit.